Military Experience and Perceptions of Parenting: A Narrative Perspective on Work-Family Balance - Robertson, Meghan M.; Black, Timothy (Canadian Journal of Counselling and Psychotherapy, 2017)
The authors of this study investigated subjectively constructed narratives of veterans’ experiences trying to balance career and parental roles. Narrative-oriented inquiry was the primary orienting methodology. Five male veterans participated in the process of coconstructing their individual first-person narratives with the primary researcher. The six stages of Arvay’s (2002) collaborative narrative method were used as the guiding framework for these narratives. Implications of these narratives with regards to future research and counselling practice are also discussed.